A comparative network analysis of eating disorder psychopathology and co-occurring depression and anxiety symptoms before and after treatment. Issue 2 (15th April 2018) - Smith, Kathryn E.; Mason, Tyler B.; Crosby, Ross D.; Cao, Li; Leonard, Rachel C.; Wetterneck, Chad T.; Smith, Brad E. R.; Farrell, Nicholas R.; Riemann, Bradley C.; Wonderlich, Stephen A.; Moessner, Markus
Abstract: Background: Network analysis is an emerging approach in the study of psychopathology, yet few applications have been seen in eating disorders (EDs). Furthermore, little research exists regarding changes in network strength after interventions. Therefore the present study examined the network structures of ED and co-occurring depression and anxiety symptoms before and after treatment for EDs. Method: Participants from residential or partial hospital ED treatment programs ( N = 446) completed assessments upon admission and discharge. Networks were estimated using regularized Graphical Gaussian Models using 38 items from the Eating Disorders Examination-Questionnaire, Quick Inventory of Depressive Symptomatology, and State-Trait Anxiety Inventory. Results: ED symptoms with high centrality indices included a desire to lose weight, guilt about eating, shape overvaluation, and wanting an empty stomach, while restlessness, self-esteem, lack of energy, and feeling overwhelmed bridged ED to depression and anxiety symptoms. Comparisons between admission and discharge networks indicated the global network strength did not change significantly, though symptom severity decreased. Participants with denser networks at admission evidenced less change in ED symptomatology during treatment. Conclusions: Findings suggest that symptoms related to shape and weight concerns and guilt are central ED symptoms, while physical symptoms, self-esteem, and feeling overwhelmed are links that may underlie comorbidities in EDs. Results provided some support for the validity of network approaches, in that admission networks conveyed prognostic information. However, the lack of correspondence between symptom reduction and change in network strength indicates that future research is needed to examine network dynamics in the context of intervention and relapse prevention.